Chlorophyll-a concentration estimation using three difference bio-optical algorithms, including a correction for the low-concentration range: the case of the Yiam reservoir, Korea. Issue 5 (3rd May 2016) - Pyo, JongCheol; Ha, SeongHyeon; Pachepsky, Yakov A.; Lee, Hyuk; Ha, Rim; Nam, Gibeom; Kim, Moon S.; Im, Jungho; Cho, Kyung Hwa
ABSTRACT: Bio-optical algorithms have been applied to monitor water quality in surface water systems. Empirical algorithms have been applied to estimate the chlorophyll- a (chl- a ) concentrations. However, the performance of each algorithm severely degrades at concentrations notably lower than 10 mg m −3 . This could be attributed to the chl- a specific absorption coefficient that became less consistent at low chl- a concentrations. Nonetheless, no effort has been made in previous studies to correct existing algorithms. In this study, we propose a correction approach to improve their performance for chl- a estimation in Yiam reservoir, Korea. Estimated chl- a concentrations of the algorithms improved after applying the correction process proposed in this study; Nash–Sutcliffe efficiency values increased from 53% to 65% and root mean square error decreased from 39% to 43%, respectively. Further research is needed to verify the correction approaches for different years or study sites.